2014
DOI: 10.1080/13563467.2014.923825
|View full text |Cite
|
Sign up to set email alerts
|

Rooted in Violence: Civil War, International Trade and the Expansion of Palm Oil in Colombia

Abstract: Internal armed conflict severely inhibits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 44 publications
2
31
0
2
Order By: Relevance
“…Advancing to Arauca en masse in August 2001, the paramilitaries’ expansion into the department preceded that of the public armed forces, a common trend in Colombia's conflict (Leech :23; WOLA :3; Verdad Abierta ; Maher ). Although operating across Arauca, the AUC established its strongest presence in Tame (Dudley ; Sierra ), as well as Cravo Norte, Fortul, and Puerto Rondón (Sierra ; WOLA :3; Amnesty International :33).…”
Section: The Department Of Araucamentioning
confidence: 99%
“…Advancing to Arauca en masse in August 2001, the paramilitaries’ expansion into the department preceded that of the public armed forces, a common trend in Colombia's conflict (Leech :23; WOLA :3; Verdad Abierta ; Maher ). Although operating across Arauca, the AUC established its strongest presence in Tame (Dudley ; Sierra ), as well as Cravo Norte, Fortul, and Puerto Rondón (Sierra ; WOLA :3; Amnesty International :33).…”
Section: The Department Of Araucamentioning
confidence: 99%
“…110-111). In other regions, the AUC have wrested control of lands through which pipelines for British Petroleum, Total, and Triton pass (Richani, 2013), and have been integral to the growth of the palm oil industry (Maher, 2015). The collusion of interests between paramilitaries, multinationals, and the state have led Richani to conclude that 'the concerns of multinational corporations intersect with the local war-system actors in their areas of operations' (Richani, 2013, p. 112) and implicate those corporations in massacres perpetrated against local populations considered 'guerrilla sympathizers'.…”
Section: Outsourcing State Violence To Paramilitariesmentioning
confidence: 99%
“…The collusion of interests between paramilitaries, multinationals, and the state have led Richani to conclude that 'the concerns of multinational corporations intersect with the local war-system actors in their areas of operations' (Richani, 2013, p. 112) and implicate those corporations in massacres perpetrated against local populations considered 'guerrilla sympathizers'. Thus, the era of neoliberal development was the golden age of paramilitarismo, facilitated by the accelerated growth of narco-trafficking and the construction of FDI mega-projects in locations close to natural resources (Oslender, 2007;Maher, 2015;Maher & Thomson, 2011).…”
Section: Outsourcing State Violence To Paramilitariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research from countries such as Sierra Leone, Colombia and Ghana has shown that large areas of land and forest traditionally used by indigenous peoples have been expropriated (Yengoh & Armah, 2015;Maher, 2014;Schoneveld et al, 2011). This phenomenon is also particularly frequent in South-East Asian countries with weak land tenure regimes (Hall, 2011;Prachvuthy, 2011).…”
Section: Negative Impact Of Palm Oil Agribusiness On Indigenous Peoplementioning
confidence: 99%